2015
DOI: 10.1007/s11270-015-2576-2
|View full text |Cite
|
Sign up to set email alerts
|

EPS and SMP as Stability Indicators During the Biofiltration of Diffuse Methane Emissions

Abstract: Biofiltration of an air stream polluted with diffuse CH 4 concentrations of 0.19 % (v v −1 ) was carried out. These emissions can be encountered at different industrial facilities such as wastewater treatment plants and landfills. The effect of ammonium supplied in the nutrient solution was studied in a range from 0 to 1 g N-NH 4 + L −1 , taking account its effect on CH 4 removal efficiency (RE), CO 2 production, ammonium conversion and the occurrence of exopolymeric substances. Additional batch assays were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The effect of ammonium (0 to 1 g/L as NH4-N) in the nutrient solution at a conventional biofilter treating an Water Environment Research, Volume 88, Number 10-Copyright © 2016 Water Environment Federation air stream with a CH4 content of 0.19% v/v was studied in regards to CH4 removal, CO2 production, ammonium conversion, and the occurrence of exopolymeric substances (Hernández et al, 2015). The results indicated increased concentrations of extracellular polysaccharide and protein when the process was not stable.…”
Section: Biological Odor/ Emissions Control Methodsmentioning
confidence: 99%
“…The effect of ammonium (0 to 1 g/L as NH4-N) in the nutrient solution at a conventional biofilter treating an Water Environment Research, Volume 88, Number 10-Copyright © 2016 Water Environment Federation air stream with a CH4 content of 0.19% v/v was studied in regards to CH4 removal, CO2 production, ammonium conversion, and the occurrence of exopolymeric substances (Hernández et al, 2015). The results indicated increased concentrations of extracellular polysaccharide and protein when the process was not stable.…”
Section: Biological Odor/ Emissions Control Methodsmentioning
confidence: 99%
“…Under non-stressing conditions, EPS productions of 0.03-0.43 g g -1 biomass using gamma methanotrophs (Methylobacter, Methylomonas) have been reported (Malashenko et al 2001). Moreover, recent studies observed that acidification, high salinity and low N concentrations positively influence EPS excretion by microorganisms, whereas EPS accumulation can be inhibit if CH4 and O2 diffusion to the cells is limited (Wilshusen et al 2004;Hernández et al 2015). In this context, a recent publication demonstrated that a consortium composed of methanotrophic and non-methanotrophic bacteria (i.e.…”
Section: Extracellular Polysaccharides and Secondary Methane-driven Bmentioning
confidence: 99%
“…Neilsen et al [6] comprehensively discussed the composition of EPS extracted from biofilms in different engineered biological systems, such as in biofilters and trickling filters. Hernández et al [10] confirmed the presence of the largest fraction of protein in EPS extracted from a methane treating biofilter and used changes in protein content as a monitoring tool to study the stress conditions. Furthermore, it was identified that protein constitutes a variety of amino acids, such as glutamic acid, aspartic acid, alanine acid and leucine acid, at a high concentration (about 40% of total proteins in EPS) [11].…”
Section: Introductionmentioning
confidence: 99%